A diesel/natural gas dual fuel mechanism constructed to reveal combustion and emission characteristics. (15th July 2019) - Zhang, Wei; Chang, Shaoyue; Wu, Wei; Dong, Lihui; Chen, Zhaohui; Chen, Guisheng
Abstract: As natural gas is an ideal alternative fuel with low cost and clean combustion, this study constructs a mechanism of diesel/natural gas dual fuel, couples it with CFD, and then discusses the effects of natural gas replacement rates on engine combustion and emission under medium load conditions. The detailed mechanism of natural gas is simplified by two methods into a reduced mechanism, which are verified to prove that it can accurately predict ignition delay, laminar flame speed, temperature and pressure. The study also combines the reduced mechanism with the 95/5vv diesel mechanism to obtain a dual-fuel mechanism. This dual fuel mechanism is verified through chemical kinetics calculations, to predict the ignition delay, laminar flame speed, important free radicals and components. Furthermore, this mechanism is verified through coupling CFD, to predict that the combustion pressure and integrated heat release agreed with the experimental data. Results show that the dual-fuel mechanism displays its correctness, effectiveness and applicability. Calculations within the range of 0–60% natural gas replacement rates indicate a regular combustion sequence; at 40% replacement rate, NO emissions goes down by 6.8%, and soot emissions decrease by 92.9%. Yet when the replacement rate of natural gas is over 55%, combustion in cylinder deteriorates. Highlights: A proposal of natural gas/diesel dual fuel mechanism. Sequential combustion in natural gas/diesel dual fuel engines is characterized. Poor diesel atomization resulting from gradual reduction of diesel injection. Ignition time and peak of heat release delayed at higher gas replacement rates. Lower NOx and soot levels caused by increasing replacement rates.